Bariatric surgery as a model to explore the basis and consequences of the Reaven hypothesis: Small, dense low-density lipoprotein and interleukin-6. (March 2019) - Adam, Safwaan; Liu, Yifen; Siahmansur, Tarza; Ho, Jan H; Dhage, Shaishav S; Yadav, Rahul; New, John P; Donn, Rachelle; Ammori, Basil J; Syed, Akheel A; Malik, Rayaz A; Soran, Handrean; et al.
Background: Reaven originally described the clustering of insulin resistance/hyperinsulinaemia, obesity (particularly visceral), altered cytokine levels, glucose intolerance, hypertriglyceridaemia and low high-density lipoprotein cholesterol. Subsequently, a potentially highly atherogenic small, dense low-density lipoprotein was also reported. We have studied the effect of bariatric surgery on this and other risk factors for atherosclerosis. Methods: Forty patients (20 with type 2 diabetes mellitus) undergoing bariatric surgery were studied before and 1 year after bariatric surgery. Results: Twelve months after bariatric surgery, median body mass index had decreased from 49.5 to 36.5 kg/m 2, fasting insulin from 21.3 to 7.8 mU/L and insulin resistance (homeostatic model assessment of insulin resistance) from 5.9 to 1.8 (all p < 0.001). Thirteen out of 20 patients had remission from type 2 diabetes mellitus. Highly sensitive C-reactive protein, interleukin-6, fasting triglycerides ( p < 0.001) and small, dense low-density lipoprotein ( p < 0.001) decreased, while high-density lipoprotein cholesterol increased ( p < 0.001) significantly, irrespective of having type 2 diabetes mellitus and/or being treated with statin therapy before surgery. Conclusion: The association between marked weight loss and change in insulin resistance and hyperinsulinaemia with the change in small, dense low-density lipoprotein and interleukin-6 warrants further investigation. Bariatric surgery provides a model for investigating the mechanisms linking insulin resistance/hyperinsulinaemia to atherosclerosis.